The Effect of Drug Consumption and Addiction on Criminal Behavior and its Prevention - Amara, Amara (Journal of Legal Studies and Researches, 2024)
Drug addiction and consumption and the crimes related to it are considered among the widespread crimes inside society. That is why, great efforts have been made to prevent it and reduce its effects by taking effective preventive measures since it leads to the spread of criminal behavior between individuals which influences negatively the society.